EFFECTIVENESS OF IMPLEMENTING THE TEACHER PROFESSION CERTIFICATION POLICY IN KEBONPEDES DISTRICT - Evi Sri Handayati; Anas Amarulloh; Fadhlu Rahman (SOSIOEDUKASI, 2024)
One crucial element in advancing education is the presence of educators with high professionalism. Considering the rough overview of the current condition of teachers, the situation is very concerning due to their low motivation and competence. Addressing this, this research aims to: (1) Examining the impact of teacher motivation on the success of teacher certification policy implementation; (2) Evaluate teacher competence in the success of implementing the teacher professional certification policy; (3) Investigate the combined influence of motivation and teacher competence on the success of implementing the teacher professional certification policy. The research analysis unit is in the Kebonpedes Subdistrict of Sukabumi Regency. The research subjects are certified teachers. A total of 66 individuals, equivalent to 50% of the total population of 132 individuals, were selected as samples. The eeffectiveness of implementing the teacher professional certification policy is proven to be influenced by the level of motivation and competence of the teachers.